2007
DOI: 10.1111/j.1600-0420.2006.00863.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative afferent pupillary defect in glaucoma: a pupillometric study

Abstract: Measuring RAPD with infrared computerized pupillometry can detect optic neuropathy in glaucoma with high sensitivity and specificity. The method is fast and objective. Pupil area amplitude measurements were superior to pupil velocity measurements for the detection of RAPD in glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 11 publications
1
26
0
2
Order By: Relevance
“…Cook et al 8 also found that combining the afferent pupil defect with direct ophthalmoscope examination for the vertical cup:disc ratio might be an adequate screening test to detect glaucoma as part of the Vision 2020 programmes in Africa. Kalaboukhova et al 22 studied the pupillary light reflex using infrared pupillometry to measure APD, and found a high sensitivity and specificity for detection of optic neuropathy in glaucoma. Our analysis lends support to these findings, given the dismal reliability seen in other studies and the sensitivity of the pupil defect and swinging flashlight test in this current study.…”
Section: Resultsmentioning
confidence: 99%
“…Cook et al 8 also found that combining the afferent pupil defect with direct ophthalmoscope examination for the vertical cup:disc ratio might be an adequate screening test to detect glaucoma as part of the Vision 2020 programmes in Africa. Kalaboukhova et al 22 studied the pupillary light reflex using infrared pupillometry to measure APD, and found a high sensitivity and specificity for detection of optic neuropathy in glaucoma. Our analysis lends support to these findings, given the dismal reliability seen in other studies and the sensitivity of the pupil defect and swinging flashlight test in this current study.…”
Section: Resultsmentioning
confidence: 99%
“…The authors indicated that every 0.1 increase in the RAPD score most likely corresponded to an inter-eye difference in RGC [91]. Application of infrared pupillometry for evaluation of RAPD in glaucoma clinic can thus serve as a sensitive, specific and objective diagnostic tool [92] and requires further validation. More recently, attention is being paid at dissecting the RGC subtypes that are preferentially lost in glaucoma.…”
Section: Relative Afferent Pupillary Defectmentioning
confidence: 99%
“…Kardon [11] berichtete, dass man bei Glaukompatienten nur wenig Korrelation zwischen dem "Pupillenfeld"-und dem Gesichtsfeldverlust sieht. Kalaboukhova et al [9] berichteten, dass die automatisierte Infrarotpupillometrie eine glaukomatöse Optikusneuropathie mit einer Sensitivität von 86,7% bei einer Spezifität von 90% detektieren kann; allerdings sind diese Werte für einen vollwertigen Screening-Test immer noch zu niedrig [9]. Andere Arbeiten, liefern dagegen optimistischere Ergebnisse [4,33].…”
Section: Pupillenperimetrie Bei Glaukomunclassified